Carrier state studies in Theileria parva infected cattle in Zimbabwe - Masaka, Samuel Musekiwa (The University of Edinburgh, 1997)
Theileriosis caused by the protozoan parasite Theileria parva, transmitted by Rhipicephalus appendiculatus ticks, is an important animal disease for the livestock industry in Zimbabwe. To characterise Zimbabwean T parva parasites, susceptible calves were infected by 3 methods; (a) subcutaneous inoculation with three T. parva ground-up-tick stabilates, (b) application of ticks collected from the field and (c) field exposure. The aim of the study was to characterise the duration of parasitaemia following infection by the 3 methods, and to compare the sensitivity of the Polymerase Chain Reaction (PCR) assay with conventional methods for detection of carrier status.

All the animals seroconverted following infection or tick exposure, as detected in the Indirect fluorescent antibody test (IF AT) for antibodies to T parva, were demonstrated to be carriers of infection by PCR for the duration of experiment, and immune to T parva A very challenge after 522 days under tick free conditions. In order to demonstrate a carrier status clean R. appendiculatus nymphs were fed on the recovered animals on 4 dates up to 456 days post infection and allowed to moult to adults and examined for infection.. Ten out of 14 animals had a carrier status that resulted in tick infections.

Cultures of Theileria infected lymphoblastoid cells were attempted from animals which developed theileriosis at Hunyani estates on field exposure. The monoclonal antibody (MAb) profile indicated infections in each case with Theileria taurotragi isolates. However, the clinical and post-mortem examination findings of the calves were typical of T. parva infection. Animals which recovered after treatment had persistent piroplasm parasitaemia and high infection prevalence in ticks applied. This implies that onward transmission in cattle occurs with this parasite, with important implications for causation of severe theileriosis in cattle. Tick infections did not occur following feeding on calves recovered from buffalo derived T parva Bally Vaughan isolate or with T. parva Avery isolete. Infections with field parasites were found to result in more efficient transmission of Theileria parasites to ticks than the Bolvac® vaccine stock; the former could be associated with the more persistent piroplasm parasitaemia in the recovered animals and the severity of the Theileria clinical reactions. PCR using p 1 04 primer sequences for rhoptry I microneme antigens of T. parva was the most sensitive indicator of carrier status. Clinical signs upon infection were not correlated with persistence of infection; carriage of parasite DNA occurred irrespective of initial severity. The IF A test was validated using sera from the carrier animals and naive animals pre-infection. The IFAT titre required to detect all infected animals was 1:160, at which the test had a specificity of only 64.63%. An IFAT cutoff titre of 1:320 resulted in a sensitivity and specificity of 90.49.% and 88.06% respectively. The current cut-off used in Zimbabwe (1 :640) resulted in 100% specificity, but sensitivity of only 64.63%. The PCR employed provided a highly sensitive method for determining T parva infection, was more sensitive than IF AT (cut-off 1 :640) and tick pick up. At least 71.7% of the samples tested post infection were positive by PCR compared to the 44% positives by IFAT at a cut-off of 1:640. Only 15% of the tick application experiments were positive compared to the 80.6% PCR positive tests and 38.9% IFAT positives when the tests were carried out synchronously.

Each of the isolates resulted in a carrier state detectable by PCR and this lasted for at least 500 days, with Theileria transmission to ticks recorded up to 456 days post infection. This is longer than recorded in previous studies in Zimbabwe. These results suggest that carrier status is the normal state following infection. Indications are that T parva Boler:U is the most suitable immunising parasite stock; although T parva Avery and Bally Vaughan infections did not result in onward transmission to ticks, these parasites are of higher pathogenicity which would be disadvantageous in vaccination.
Keywords: protozoan parasite; livestock; parasitaemia; Polymerase Chain Reaction; PCR; Indirect fluorescent antibody test; IFAT; R. appendiculatus